Islam, women labor and economic development - Siti Nur Azizah; Abdul Qoyum; Prasojo Prasojo (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
The purpose of this paper is to find out the position of female workers in Islam, and the role of women in building prosperity for themselves, surrounding communities and participating in the nation's economic development. It is undeniable that women in Muslim countries lag behind their counterparts in non-Muslim countries in terms of participation in the workforce. However, a large number of studies show that religion is not the culprit in preventing women from being active in the labor market, but rather the cultural attitude that shapes labor force participation decisions. In the author's view, one way for women to achieve prosperity is to give them the opportunity to work. For women, the goal is to provide opportunities to work not only to increase income but also to manage various social vulnerabilities, especially poverty and domestic violence. Women's access to work also means the opportunity to engage in broader socio-political relations. This means that women can contribute to the development of their environment because they no longer live in the household environment, but have enough time to interact in the public space to transform social capital into economic capital in the form of opportunities to engage in economic activities. However, the effort to convert social capital into economic capital is not easy. There are still unfavourable views on the grounds that women's abilities are not commensurate with men which ultimately limits women from accessing livelihoods. Therefore, it is necessary to find a perspective that places men and women in an equal and fair position, especially in acquiring, utilizing, and developing assets and access to economic resources. It is time for the state to formulate public policies that place women as the main actors and not only as objects or complementary policies. In this paper we conclude that the importance of the role of the government through the integration of formal and Islamic education methods to the rearrangement of the labour market, so that women better understand the market and participatory communities become convinced to support women's labour force participation.The purpose of this paper is to find out the position of female workers in Islam, and the role of women in building prosperity for themselves, surrounding communities and participating in the nation's economic development. It is undeniable that women in Muslim countries lag behind their counterparts in non-Muslim countries in terms of participation in the workforce. However, a large number of studies show that religion is not the culprit in preventing women from being active in the labor market, but rather the cultural attitude that shapes labor force participation decisions. In the author's view, one way for women to achieve prosperity is to give them the opportunity to work. For women, the goal is to provide opportunities to work not only to increase income but also to manage various social vulnerabilities, especially poverty and domestic violence. Women's access to work also means the opportunity to engage in broader socio-political relations. This means that women can contribute to the development of their environment because they no longer live in the household environment, but have enough time to interact in the public space to transform social capital into economic capital in the form of opportunities to engage in economic activities. However, the effort to convert social capital into economic capital is not easy. There are still unfavourable views on the grounds that women's abilities are not commensurate with men which ultimately limits women from accessing livelihoods. Therefore, it is necessary to find a perspective that places men and women in an equal and fair position, especially in acquiring, utilizing, and developing assets and access to economic resources. It is time for the state to formulate public policies that place women as the main actors and not only as objects or complementary policies.In this paper we conclude that the importance of the role of the government through the integration of formal and Islamic education methods to the rearrangement of the labour market, so that women better understand the market and participatory communities become convinced to support women's labour force participation.